The Evaluation of Endotracheal Intubation Effect on Blood Flow Stability Parameters in Baghdad and Gazzi AL-Harriri Hospitals - Azhar A. Mhaibes (Journal of Techniques)
Endotracheal intubation and laryngoscopy have become necessary to provide sufficient airway management, deliver anesthesia and avoid aspiration in anesthetized individuals. Laryngoscopy and intubation have been shown to induce a broad spectrum of stress responses e.g. hypertension and tachycardia. The current study aimed to assess the impact of endotracheal intubation on the pulse rate (P.R) and blood pressure (B.P) during different time intervals of general anesthesia. This study was performed in Baghdad teaching and Gazzi AL-Harriri hospitals during 2019-2020.  A total of fifty (50) patients were included in the study; twenty-five (25) were females and twenty-five (25) males with American society of anesthesiologist (ASA) physical status (I & II). The ages of patients ranged between (16-60) years.  All patients were administrated (I.V.) Dexamethasone (0.11 mg/kg), Metoclopramide (0.14mg/kg), Ranitidine (0.71mg/kg) & Ketamine (0.5 mg/kg) as premedication. At the induction of anesthesia, patients were administrated (2-3 mg/kg) Propofol as a hypnotic drug and succinylcholine 1 mg/kg as a muscle relaxant. The results revealed a significant increase (p≤0.05) in systolic/ diastolic blood pressure (B.p) at- intubation (135.58 ± 10.29 / 91.74 ± 10.91) and also at 1 minute (132.34 ± 10.08 / 88.58 ± 13.06 ). There was also a significant increase (p≤0.05) in pulse rate (P.R) at-intubation (103.00 ± 18.59).